2014
DOI: 10.1017/cbo9781139923279
|View full text |Cite
|
Sign up to set email alerts
|

Scribal Correction and Literary Craft

Abstract: This extensive survey of scribal correction in English manuscripts explores what correcting reveals about attitudes to books, language and literature in late medieval England. Daniel Wakelin surveys a range of manuscripts and genres, but focuses especially on poems by Chaucer, Hoccleve and Lydgate, and on prose works such as chronicles, religious instruction and practical lore. His materials are the variants and corrections found in manuscripts, phenomena usually studied only by editors or palaeographers, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This sentiment prevailed into the seventeenth century, when Sir Edward Coke-Lord Chief Justice of the King's Bench and foremost jurist of the early modern era-noted in his seminal Institutes of the Laws of England the necessity that deeds were written on a durable material such as parchment "for the writing upon these is least liable to alterations or corruption" [9]. Wakelin's [39] survey of scribal correction found that in Tudor Royal accounts (documents likely written on sheepskin parchment) errors during writing were not scraped away and overwritten but crossed out and interlineation inserted between sentences, perhaps in acknowledgement of this risk.…”
Section: Discussionmentioning
confidence: 99%
“…This sentiment prevailed into the seventeenth century, when Sir Edward Coke-Lord Chief Justice of the King's Bench and foremost jurist of the early modern era-noted in his seminal Institutes of the Laws of England the necessity that deeds were written on a durable material such as parchment "for the writing upon these is least liable to alterations or corruption" [9]. Wakelin's [39] survey of scribal correction found that in Tudor Royal accounts (documents likely written on sheepskin parchment) errors during writing were not scraped away and overwritten but crossed out and interlineation inserted between sentences, perhaps in acknowledgement of this risk.…”
Section: Discussionmentioning
confidence: 99%
“…14 As well as translations, a number of continuations and adaptations of the Prose Brut were composed throughout the Middle Ages: the authors of these continuations may have seen their work as an act of restoration, rather than invention. 15 Downside 78291 has one such continuation, and although the end of the text is cut away, it is likely to be the version that finishes in 1437, ending with the murder of James I of Scotland. 16 The sheer number of variations across extant Prose Brut manuscripts has led to difficulties in classifying these chronicles.…”
Section: The Prose Brut and The Latin Prose Brutmentioning
confidence: 99%